Historical evidence and argument - Henige, David P. (ACLS Humanities E-Book., 2005)
Historians know about the past because they examine the evidence. But what exactly is "evidence," how do historians know what it means--and how can we trust them to get it right? Historian David Henige tackles such questions of historical reliability head-on in his skeptical, unsparing, and acerbically witty Historical Evidence and Argument. "Systematic doubt" is his watchword, and he practices what he preaches through a variety of insightful assessments of historical controversies--for example, over the dating of artifacts and the textual analysis of translated documents. Skepticism, Henige contends, forces us to recognize the limits of our knowledge, but is also a positive force that stimulates new scholarship to counter it.--Publisher description.